A fluorosurfactant and photoreducible CuII-tren click catalyst: surfactant and catalytic properties at liquid/liquid interfaces. Issue 45 (22nd October 2015) - Jochyms, Quentin; Guillot, Pierre; Mignard, Emmanuel; Vincent, Jean-Marc
Abstract : The fluorous copper(ii )-tren complex2 is a powerful surfactant which strongly reduces the perfluorodecalin/water and diisopropyl ether/water interface tensions. When photoreduced by light it catalyzes the Huisgen click cycloaddition. Abstract : The fluorous copper(ii ) complex [Cu II (trenRf6 )3-benzoylbenzoate]3-benzoylbenzoate2, composed of a highly fluorophilic tris(2-aminoethyl)amine ligand and two 3-benzoylbenzoates as counterions and photosensitizers, was synthesized from the dinuclear complex [CuII2(3-benzoylbenzoate)4 (H2 O)2 ]1 which was characterized by X-ray analysis. Complex2, which is highly soluble in perfluorocarbons, moderately soluble in organic solvents while insoluble in water, was found to be a very effective fluorosurfactant. At the air/water interface it formed a Langmuir film, which upon compression slowly collapsed at about 28 mN m −1, which corresponds to a surface area of about 220 Å 2 per molecule. Tensiometric measurements revealed that2 is more rapidly adsorbed at the diisopropyl ether (DIPE)/water interface than the perfluorodecalin (PFD)/water one, leading to a decrease of the interfacial tensions of about 14 mN m −1 and 40 mN m −1, respectively. Photoreduction of2 occurs effectively in H-donating solvents such as THF and DIPE, or even in PFD ensuring that an electron donor, such as propargyl alcohol, is present in a separate aqueous phase. Complex2, when combined with light (365 nm), catalyzes the click reaction between the azide3 and alkyne4 under homogeneous conditions (methanol), to afford the disaccharide5 . Under emulsified biphasic DIPE/water or PFD/water conditions, the reactions proceeded well. However, it was shown that a fast and significant amount of copper and 3-benzoylbenzoate counterion was transferred into the aqueous phase, and that most of the catalysis could be ascribed to a copper species solubilised in the aqueous phase, and not to the fluorous copper complex accumulated at the interface.